Validation of modeled daily erythemal exposure along tropical and subtropical shipping routes by ship‐based and satellite‐based measurements. Issue 9 (5th May 2015) - Feister, Uwe; Meyer, Gabriele; Laschewski, Gudrun; Boettcher, Christopher
Abstract The Personal ERythemal EXposure (PEREX) model for seafarers working on decks of vessels has been developed to be used for retrospective estimates of personal occupational erythemal exposure in dependence of work profile, time period, and sea route. Extremely high UV index values up to 22 and daily erythemal exposure up to 89 standard erythemal dose have been derived from ship‐based measurements in tropical oceans. Worldwide climatological maps of daily solar erythemal exposure derived from 10 year (2004–2013) hourly grid point radiative transfer model calculations for both cloudless sky and cloudy sky serve as the database of PEREX. The PEREX database is compared with ship‐based measurements taken along four routes of merchant vessels, continuous UV radiation measurements taken on the research vessel Meteor on its mainly tropical and subtropical routes for 2 years, daily cloudless‐sky erythemal exposure derived from 10 min LibRadtran radiative transfer model calculations, and 2 years of satellite‐based erythemal exposure data of the Ozone Monitoring Instrument on the Aura satellite along the ship routes. Systematic differences between PEREX model data, ship‐based data, and satellite‐based daily erythemal exposure for all‐sky conditions are only 1 to 3%, while short‐term variations of cloudiness result in standard deviations of differences around 30%. Measured ratios between cloudless‐sky erythemal radiation at vertical to horizontal incidence decrease with decreasing solar zenith angle, while clouds flatten their diurnal course.